The Impact of Inclusive Education on Learners with Disabilities in High Schools of Harare, Zimbabwe - Chuchu, Tinashe; Chuchu, Vimbai (Journal of Social and Development Sciences, 2016)
The problem of low inclusive education is essential to research as it highlights the importance of equal opportunity to all students regardless of mental or physical ability. The study was conducted within a Zimbabwean high school context. The purpose of the study was to conduct an empirical investigation into the impact of inclusive education and therefore establish the extent to which it has benefited students with disabilities in four high schools in the Harare province. Furthermore, study’s intention was to therefore propose a theoretical framework that could be used to address low success in inclusive education. The methodology was qualitative in nature and interviews were used to collect research data. Quota sampling was adopted in selection of suitable respondents. It was observed that a lack of financial and human resources, as well as effective policies had contributed to the low impact of inclusive education in high schools in Harare, Zimbabwe. In conclusion the results also revealed that inclusive education in high schools in Harare had not made much of an impact due to negative perceptions and attitudes of the people that are pivotal to its success.